THE CORRELATION BETWEEN STUDENTS’ LEARNING STYLES AND STUDENTS’ ACHIEVEMENT IN LISTENING AND SPEAKING SKILLS (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2024)
The purpose of this study is to investigate the learning style tendencies exhibited by students in their pursuit of listening and speaking skills for general communication at UKI Toraja, as well as to examine the correlation between these learning style tendencies and their achievement in speaking and listening skills. This research employed a quantitative descriptive approach, with a sample size of 35 students, analyzed using SPSS 26. The results of the questionnaire indicated a very strong correlation, ranging from 0.80 to 1.000. It revealed that students possessed three distinct learning styles when acquiring listening and speaking skills for general communication: visual, auditory, and kinesthetic. Each of these learning styles exhibited a highly significant correlation with students' achievements. Specifically, the correlation between the visual learning style and student achievement was 0.932, signifying a very strong relationship. The audio learning style exhibited a correlation of 0.885 with student learning achievement, also indicating a very strong connection. Lastly, the kinesthetic learning style displayed a correlation of 0.930 with student achievement, further underscoring a very strong relationship. These findings demonstrate that each learning style (visual, auditory, kinesthetic) is significantly correlated with student achievement. Therefore, it can be concluded that H1 is accepted, as each learning style exhibits a strong correlation with students' achievement in listening and speaking skills
Keywords: Listening and speaking for general communication; Correlation; Students Achievement.